Parents/responsible co-advances in the oral health of your children (Research, Society and Development, 2020)
To verify the level of knowledge of parents and guardians about dentistry in early childhood, and to analyze sociodemographic variables. This was a field research, observational and cross-sectional with quantitative approach and descriptive and analytical analysis of the data, through questionnaires, which were applied to parents / guardians of children from 0 to 3 years old from municipal daycare centers a city of the Paraíba hinterland. 171 parents or guardians of children enrolled in municipal public day care centers were interviewed. Most of them were predominant females (91.2%), aged 15 to 30 years (63.2%), with monthly family income of up to R $ 780.00 (67.3%), and had predominant education level of elementary school I (33.9%). Most parents / guardians (55.6%) considered that oral health meant hygiene and were aware of the existence of dentistry for babies (64.9%). For 52.6% of respondents, the ideal time to start hygiene of the baby's oral cavity is from the birth of the first tooth and on the method used to perform this hygiene, 53.8% indicated gauze or diaper soaked in filtered water. It was observed that 53.8% reported that the importance of oral hygiene is related to the overall health of the baby. Parents and /or guardians of public daycare infants centers demonstrated a reasonable knowledge regarding children's oral health.